Membrane-bound tubulin in brain and thyroid tissue. - B. Bhattacharyya; Jean‐Nicolas Volff (1975)
Brain and thyroid tissue contain membrane-bound colchicine-binding activity that is not due to contamination by loosely bound cytoplasmic tubulin. This activity can be solubilized to the extent of 80 to 90% by treatment with 0.2% Nonidet P-40 with retention of colchicine binding. Extracts so obtained contain a prominent protein band in disc gel electrophoresis that co-migrates with tubulin. Membranes, and the solubilized protein therefrom, exhibit ligand binding properties like tubulin; for colchicine the KA is approximately 1 X 10(6) M-1 in brain and approximately 0.6 X 10(6) M-1 in thyroid; for vinblastine the KA is approximately 8 X 10(6) M-1 for both tissues; and for podophyllotoxin the Ki is approximately 2 X 10(-6) M for both tissues. Displacement by analogues of colchicine is of the same order as for soluble tubulin. Although membrane-bound colchicine-binding activity shows greater thermal stability and a higher optimum binding temperature (54 degrees versus 37 degrees) than soluble tubulin, this appears to be the result of the membrane environment since the solubilized binding activity behaves like the soluble tubulin. Antibody against soluble brain tubulin reacts with membranes and solubulized colchicine-binding activity from both brain and thyroid gland. We conclude that brain and thyroid membrane preparations contain firmly bound tubulin or a very similar protein.